Development associated profiling of chitinase and microRNA of Helicoverpa armigera identified chitinase repressive microRNA - Agrawal, Neema (Nature Publishing Group, 2013)
Expression of chitinase is developmentally regulated in insects in consonance with their molting process. During the larval-larval metamorphosis in Helicoverpa armigera, chitinase gene expression varies from high to negligible. In the five-day metamorphic course of fifth-instar larvae, chitinase transcript is least abundant on third day and maximal on fifth day. MicroRNA library prepared from these highest and lowest chitinase-expressing larval stages resulted in isolation of several miRNAs. In silico analysis of sequenced miRNAs revealed three miRNAs having sequence similarity to 3′UTR of chitinase. Gene-targeted specific action of these miRNAs, was investigated by luciferase reporter having 3′UTR of chitinase. Only one of three miRNAs, miR-24, inhibited luciferase expression. Further, a day-wise in vivo quantification of miR-24 in fifth-instar larvae revealed a negative correlation with corresponding chitinase transcript abundance. The force-feeding of synthetic miR-24 induced significant morphological aberrations accompanied with arrest of molting. These miR-24 force-fed larvae revealed significantly reduced chitinase transcript abundance.